Optimal CW-Doppler derived parameter for the diagnosis of iatrogenic mitral stenosis during transcatheter edge-to-edge repair for mitral regurgitation. (3rd October 2022) - Kassar, M; Madhkour, R; Praz, F; Hunziker, L; Windecker, S; Brugger, N
Abstract: Introduction: Transcatheter Edge-to-Edge repair (TEER) for mitral regurgitation (MR) is a minimal invasive alternative to surgery for high risk patients. One of the principal disadvantage is the risk of creating a stenosis (MS). The optimal parameter and its cut-off to monitor mitral valve area (MVA) during TEER is currently not defined and usually only the mean transmitral gradient (Gd) is used. Method: 116 patients with complete 3D MVA measurements and CW-Doppler derived mean and maximal diastolic transmitral Gd, and pressure half time (PHT) before the intervention and after each TEER device implantation were included in this study. A clinically significant MS was defined as a 3D MVA <1.5 cm 2 according to the ESC guidelines. Because the mean Gd is known to be extremely dependent on the heart rate (HR) this parameter was "normalized" for a frequency of 60/min: norm. mean Gd = (mean Gd/HR) × 60. The accuracy of the different CW-derived parameters to diagnose or predict a MS was evaluated using a ROC analysis. Results: 47% of the patients suffered from a secondary MR, 53% were treated with one device and 47% with two. According to the 3D MVA measurements, after one device 16 and after two devices 12 patients had a clinically significant MS. The ROC analyses for the diagnosis of a significant MS after one device (Figure 1) show a maximal AUC of 0.99 for PHT with an optimal cut-off of 151ms (sensitivity 94%, specificity 95%), followed by norm. mean Gd (AUC 0.96, 3.16mmHg, 100%, 82%), mean Gd (AUC 0.92, 3.6mmHg, 88%, 83%) and max. Gd (AUC 0.92, 8.5mmHg, 94%, 83%). Combining three different cut-offs (PHT 164ms or norm. mean Gd 4.7mmHg or max. Gd 12mmHg) a sensitivity of 100% and a specificity of 98% was achieved. The prognostic value of these same parameters to predict a MS after two devices was much less optimal according to the ROC analyses: PHT, AUC 0.82, 100ms, 83%, 59%; norm. mean Gd AUC 0.73, 2.8mmHg, 67%, 81%; mean Gd AUC 0.70, 2.4mmHg, 83%, 51%; max. Gd AUC 0.69, 8.4mmHg, 50%, 85%. The diagnostic value of the CW-derived parameters measured after the implantation of two devices to detect a MS was better (Figure 2): PHT, AUC 0.92, 142ms, 92%, 78%; norm. mean Gd, AUC 0.87, 3.4mmHg, 92%, 73%; mean Gd, AUC 0.81, 3.9mmHg, 92%, 71%; max. Gd AUC 0.74, 8.6mmHg, 83%, 66%. The cut-offs for PHT without false negative and with the maximal specificity were: 140ms (specificity 86%) to diagnose a MS after one device, 93ms (specificity 56%) to predict a MS after a second device implantation and 133ms (specificity 63%) to detect a MS after two devices. Conclusion: PHT is the most accurate CW-derived parameter to diagnose or make a prognostic of clinically significant mitral stenosis after TEER. Given the possible disastrous consequence of a iatrogenic stenosis, these parameters should only be used with cut-offs offering a sensitivity of 100% and when a value above these limits is measured, then decisions should be based of 3D MVA measurements. Funding Acknowledgement: Type of funding sources: None.